Data analysis of random blood measurements for abnormal condition detection - Sokol, Yevgen; Shchapov, Pavel; Tomashevskyi, Roman; Veligorskyi, Oleksandr; Picking, Richard; Chakirov, Roustiam (2017 Internet Technologies and Applications (ITA), 2017)
This paper discusses an approach of the abnormal condition detection of whole blood using piezo-synthetic effects in blood under dynamic external pressure. Three groups of samples having verified chemical and biological conditions were analysed to prove reliable detection: saline, whole blood and whole blood with colorectal cancer as an example of abnormal conditions. The procedure of a discrete differentiation process for obtained experimental data has been proposed as preliminary processing. Three information parameters have been selected to describe experimental data. Fischer F-statistics were used to determine the information content of the proposed information parameters. It has been proved that the proposed information parameters react on changing state of object under test and therefore can be effectively used for the abnormal condition detection.